Metabolomics and Exercise: possibilities and perspectives - Renata Garbellini Duft; Alex Castro; Mara Patrícia Traina Chacon-Mikahil; Cláudia Regina Cavaglieri (Universidade Estadual Paulista (UNESP), 2017)
Abstract Aim This review aimed to provide an overview of the publications using metabolomics in research with physical exercises and to demonstrate how researchers have been applying this approach. Methods A systematic search in the databases Web of Science, SCOPUS and PubMed was performed, with the key words: "metabolomics" OR "metabonomics" and with "metabolomics" OR "metabonomics" AND "exercise" in the title or abstract of the articles. The search period was from 2000 to 2016. Forty-four original articles were selected. The studies found were separated into four categories: metabolic responses to physical exercise, supplementation and physical exercise, sports performance, and physical exercise related to diseases. Results It was possible to observe the exponential growth of the use of this approach in Sports and Health Sciences, and the four sub-fields towards which these researches involving exercise are directed, enabling a more comprehensive characterization of different metabolic profiles, as well as their study for identifying new biomarkers related to physical exercise. Conclusions The possibilities of using metabolomics approach are increasing in the fields of Health Sciences, Sports, and Physical Activity. The experimental design of the study is essential to take advantage of this tool and be able to answer questions in the metabolism comprehension.